Production of Vernacular Catechisms in Early Modern Königsberg (1545–1575), Its Dynamics and Goals Defined by the Print Agents - Kordyzon, Wojciech (Knygotyra, 2023)
This paper discusses the development of the vernacular catechism as a printed genre. The process is exemplified by the editions published in Königsberg between 1545 and 1575 where the catechisms were printed in several vernacular languages (German, Lithuanian, Polish, Prussian) in printing shops run by Hans Weinreich, Aleksander Aujezdecki, and Hans Daubmann. The paper seeks to analyse the material in terms of linguistic coverage in the Duchy of Prussia and, via analysis of the peritextual elements, how the print agents presented their work to the recipients. The aspects of book design, such as the volume, format, and decorations, are included in the analysis to indicate the intended book prestige and usage.